Use of bacterial cellulose in closure of nasal septal perforation - Mandour, Yasser Mohammad Hassan; Fahmy Shendy, Mohammed; Badie, Samer; Elrefai, Ahmed; Mohammed, Samira; Abdel Menem, M. O. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: 30 patients with nasal septal perforation after surgical correction of septal deviation undergoing trials of septal closure were divided into 2 groups to compare between results of free inferior turbinate graft with bacterial cellulose and results of free inferior turbinate graft only in closure of nasal septal perforation. To compare between results of free inferior turbinate graft with bacterial cellulose and results of free inferior turbinate graft only in closure of nasal septal perforation. Methods: Prospective randomized study in which 30 patients with nasal septal perforation after surgical correction of septal deviation undergoing trials of septal closure were divided into 2 groups; group I (15 patients) in which free inferior turbinate graft with bacterial cellulose would be used in closure of nasal septal perforation; group II (15 patients) in which free inferior turbinate graft only would be used in closure of nasal septal perforation. Results: Septal perforation healing (closure) would be in 10 patients in group I while in 6 patients in group II. Improvement in nasal obstruction, crustion, epistaxis and breathing sound in group I would be better than in group II. Conclusions: Use of free inferior turbinate graft with bacterial cellulose would be an effective method than use of free inferior turbinate graft only in closure of nasal septal perforation.